Mechanisms of synovial macrophage polarization in osteoarthritis pathogenesis and their therapeutic implications - Zhang, Kun; Wang, Zheng; He, Jiaqi; Lu, Liuru; Wang, Wenshu; Yang, Aiwei; Xie, Huayi; Huang, Linhui; Huang, Yuying; Zhang, Ke; Jiang, Mingyang; Wei, Ruqiong (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a degenerative joint disease characterized by synovial inflammation, cartilage degradation, and subchondral bone remodeling. Synovial macrophages, particularly their polarization into pro-inflammatory M1 or anti-inflammatory M2 phenotypes, play a pivotal role in OA pathogenesis. M1 macrophages drive synovitis, oxidative stress, and cartilage catabolism by secreting cytokines (IL-1β, TNF-α) and matrix-degrading enzymes (MMPs, ADAMTS-5), while M2 macrophages promote tissue repair via TGF-β and IL-10. Emerging therapeutic strategies, such as macrophage depletion, mTOR/SIRT1 modulation, and M2 polarization, demonstrate potential in rebalancing the M1/M2 ratio to attenuate OA progression. However, translating these macrophage-targeted strategies into clinical practice remains challenging due to difficulties in achieving subtype-specific targeting, avoiding off-target immune effects, and ensuring consistent therapeutic efficacy across patient populations. However, challenges remain in achieving subtype-specific targeting and translating preclinical findings to clinical applications. This review summarizes current knowledge and provides valuable insights for advancing OA management strategies, underscoring macrophages as promising therapeutic targets in osteoarthritis.